Neutrosophic Aggregation (INPOWA) Operator for Empirical Insights into Teaching Value: A Case Study of College English Instruction in Higher Education - Ting Li (Neutrosophic Sets and Systems)
In the evolving educational landscape, the emphasis on quality assurance in English instruction at the higher education level has gained renewed urgency. As English functions as a global lingua franca, institutions must ensure that their teaching strategies are effective, responsive, and capable of equipping students with both linguistic and critical thinking competencies. This study investigates the dimensions influencing teaching quality in English instruction within universities, focusing on pedagogical, institutional, and student-centered variables. Using a multidimensional evaluation framework, we explore real-world instructional practices and identify performance disparities across diverse models. This study uses the decision-making methodology with two methods, such as ITARA and COPRAS to obtain the weights of factors and ranking the options. These methods are used under the Interval valued Neutrosophic Numbers to dela with uncertainty information. We use the Prioritized Ordered Weighted Aggregation (POWA) Operator to combine the different Neutrosophic numbers. The findings offer empirical insights into effective teaching methodologies and highlight pathways for continuous pedagogical improvement and institutional development.